2015
DOI: 10.1063/1.4932517
|View full text |Cite
|
Sign up to set email alerts
|

Thickness dependence of La0.7Sr0.3MnO3/PbZr0.2Ti0.8O3 magnetoelectric interfaces

Abstract: Magnetoelectric materials have great potential to revolutionize electronic devices due to the coupling of their electric and magnetic properties. Thickness varying La 0.7 Sr 0.3 MnO 3 (LSMO)/ PbZr 0.2 Ti 0.8 O 3 (PZT) heterostructures were built and measured in this article by valence sensitive x-ray absorption spectroscopy. The sizing effects of the heterostructures on the LSMO/PZT magnetoelectric interfaces were investigated through the behavior of Mn valence, a property associated with the LSMO magnetizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 37 publications
0
16
1
Order By: Relevance
“…Growth parameters are discussed in the Methods section 16 . Multiple thicknesses were measured within the range of 1–16 u.c.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Growth parameters are discussed in the Methods section 16 . Multiple thicknesses were measured within the range of 1–16 u.c.…”
Section: Resultsmentioning
confidence: 99%
“…To better understand the observed thickness-dependent change in valence, we fit both FY and TEY data using a layer-dependent valence model developed in a previous work 16 . The fit to the experimental data is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thin films of the doped perovskite manganites, La 1− x Sr x MnO 3 , have attracted considerable great attention due to their fascinating physical properties . The transport properties of La 1− x Sr x MnO 3 films are sensitive to the film thickness and the lattice strain.…”
Section: Introductionmentioning
confidence: 99%
“…The authors concluded that a large magnetoelectric response in LSMO/PZT films was most likely produced by a modified interfacial spin configuration [7]. Zhou et al measured the effective valency of Mn atoms in LSMO/PZT heterostructures using valence sensitive x-ray absorption spectroscopy [19]. The measurements showed that the Mn valency increased with increasing thickness of the LSMO and PZT films.…”
Section: Introductionmentioning
confidence: 99%